Legal Analysis of Organ Donation Regulations Under Indonesian Positive Law - V.Junaedi; W.Kurniawan (The Medical Journal of Hospital Management and Health Law, 2024)
Introduction: Organ transplantation represents a pinnacle of modern medical achievement, yet its execution is heavily contingent upon a robust legal framework that ensures ethical compliance and prevents illicit practices. In Indonesia, the demand for organ donors consistently outpaces supply, creating a critical need for a comprehensive legal analysis of current regulations. This study examines the legal landscape governing organ donation within the Indonesian positive law framework to evaluate its adequacy and protective mechanisms. Methods: This research employs a normative juridical method, analyzing primary legal sources, including statutory legislation, government regulations, and relevant health acts, alongside secondary legal materials such as academic journals and legal commentaries. Results: The findings indicate that while Indonesian law, primarily through the Health Act (Undang-Undang Kesehatan), explicitly permits altruistic organ donation and strictly prohibits commercialization, significant regulatory gaps persist. The statutory mechanisms lack detailed operational procedures regarding donor registry, consent verification, and post-mortem procurement protocols, leading to ambiguity in enforcement and clinical implementation. Discussion: The literature review reveals a profound divergence between legislative intent and practical execution, where the absence of a centralized national regulatory body exacerbates vulnerabilities to organ trafficking. Ethical concerns intersect with legal loopholes, particularly regarding the determination of brain death and the exact boundaries of familial consent. Conclusions: Indonesian positive law requires immediate legislative updates, specifically the enactment of detailed government regulations establishing an independent oversight authority and a transparent national donor registry.